STUDI TEORETIS PERUBAHAN TRANS-HCOH MENJADI H2CO MELALUI QUANTUM TUNNELING DENGAN DFT DAN PENDEKATAN WKB - RIZKA NUR FADILLA, 081311333055 (2016)
This research is conducted to study the stability of trans-HCOH molecule using density-functional theory (DFT). Experimentally, trans-HCOH rearranges to H2CO with half-life two hours in temperature at 11K whereby quantum tunneling makes the rearrangement possible. The study is started from determination of reaction path from trans-HCOH to H2CO followed by its corresponding energy barrier using DFT. Then, Wentzel-Kramers-Brillouin (WKB) approximation is used to get probability of quantum tunneling hence the rearrangement rate and the half-life can be calculated. To prove the rearrangement is not triggered by internal thermal energy, the rearrangement rate is calculated based on the Arrhenius equation. The calculations predict the half-life of trans-HCOH is 2.5 hours via quantum tunneling and infinity via internal thermal energy which agrees with the experiment.